2016
DOI: 10.5551/jat.31401
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Angiotensin II Type 1 and 2 Receptors in Gelatinase Regulation in Human Carotid Atheroma <i>in vitro </i>

Abstract: Aim: Matrix metalloproteinases (MMPs), angiotensin II (AII) and its receptors are implicated in atherosclerotic plaque instability, however the roles of the two receptor subtypes, ATR1 and ATR2, in MMP regulation remain uncertain. In this study, we investigated the effect of ATR1 and ATR2 blockade on the expression and activity of MMP-2, MMP-3 and MMP-9, in human carotid atheroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…However, our data at least indicated that ANG II‐AT 1 R axis played important roles in EAM development and CD11b + Ly6C + cells reprogramming. And our data also were in line with published reports that most actions of ANG II were primarily carried out by AT 1 R signaling . Additionally, inhibition of Erk1/2, p38, or Stat3 could also obviously ameliorate the cardiac injury, which cannot completely owe to prevent M1 polarization; as all these inhibitors are not specific for macrophage polarization, more and more data indicated that macrophage polarization was associated with Erk1/2, p38, or Stat3; therefore, our data suggested that to prevent the macrophage polarization, the EAM development could be ameliorated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our data at least indicated that ANG II‐AT 1 R axis played important roles in EAM development and CD11b + Ly6C + cells reprogramming. And our data also were in line with published reports that most actions of ANG II were primarily carried out by AT 1 R signaling . Additionally, inhibition of Erk1/2, p38, or Stat3 could also obviously ameliorate the cardiac injury, which cannot completely owe to prevent M1 polarization; as all these inhibitors are not specific for macrophage polarization, more and more data indicated that macrophage polarization was associated with Erk1/2, p38, or Stat3; therefore, our data suggested that to prevent the macrophage polarization, the EAM development could be ameliorated.…”
Section: Discussionsupporting
confidence: 91%
“…ANG II plays pivotal physiological or pathological roles through ligation with its specific G protein‐coupled receptors, type 1/2 receptor (AT 1 R or AT 2 R). However, most roles were carried out by AT 1 R signaling . Recently, ANG II can serve as a powerful proinflammatory mediator and involve in autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus, autoimmune nephritis, and experimental autoimmune encephalomyelitis as well as monocyte and macrophage recruitment .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, inflammatory cells (neutrophils, B- and T-lymphocytes), MMPs and proinflammatory cytokines will be assessed by immunohistochemistry and ELISA as previously described [40, 41]. Circulating concentrations of other AAA biomarkers, including osteoprotegerin, resistin, D-dimer and fasting lipids, will be assessed by ELISA and automated assays as previously described [31, 3638].…”
Section: Methodsmentioning
confidence: 99%
“…In the past decades, the concept of the “vulnerable plaque” has been dominant in the pathogenesis, diagnosis and treatment of ACS, and autopsy studies consistently found that plaques of this morphology were responsible for the majority of fatal myocardial infarcts. A large number of studies indicated that rupture of TCFA is related to the increased breakdown and decreased synthesis of interstitial collagen that forms the fibrous cap [ 10 ]. Interstitial collagen produced by vascular smooth muscle cells (VSMCs) provides strength to the fibrous cap of the plaque.…”
Section: Plaque Rupturementioning
confidence: 99%